Peran Notaris dalam Pendaftaran Badan Usaha Berbentuk Persekutuan Komanditer, Persekutuan Firma, dan Persekutuan Perdata - Sari, Dian Rosita (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2025)
Following the enactment of Regulation of the Minister of Law and Human Rights No. 17 of 2018, the role of the notary is to regulate the obligation of business entities, such as limited partnerships (CV), firms, and civil partnerships, to register their companies with the Minister through the Business Entity Administration System. The research method used is normative law (normative jurisprudence) with a legal approach, namely a legislative conceptual approach. Normative law research is a literature review, and the results are analyzed descriptively. If all the requirements and supporting conditions are met, the Notary is authorized to make an authentic deed and on behalf of the applicant, the notary submits an application for the registration of the establishment, amendment of the articles of association, dissolution of non-legal entities in the form of limited partnership (CV), firm and Civil Partnership to the Business Entity Administration System. Furthermore, in drafting authentic deeds pursuant to the Commercial Code (KUHD), the Civil Code (KUHPerdata), the Notary Law (UUJN), and the Regulation of the Minister of Law and Human Rights No. 17 of 2018, the notary bears responsibility for any errors that occur during data entry in SABU. Should such an error arise, the notary is obligated to report it to the Directorate General of General Legal Administration (AHU) to facilitate the correction of the recorded data.